Wind Tunnel testing of small Vertical-Axis Wind Turbines in Turbulent Flows. (2017) - Molina, Andreu Carbó; Bartoli, Gianni; de Troyer, Tim
Abstract: This study presents an innovative wind tunnel approach to evaluate the efficiency of Vertical-Axis Wind Turbines (VAWT) in turbulent flows, to study their integration in urban environments. The first part of the research is devoted to obtaining highly-turbulent wind profiles in the wind tunnel, with the use of different configurations of square grids. A careful study and validation of this technique is done, in order to obtain uniform wind conditions with the adequate values of turbulence intensity and length scales to model the urban flows. The set-up is used to test a H-Darrieus VAWT under values of turbulence over 5%, in comparison with the operation of the turbine under free stream. The preliminary results show that high levels of turbulence do have a significant effect in turbine performance, causing a drop of power for high rotational speeds, increased vibrations in the structure and more difficult control of the rotor. More tests are advised to validate these observations, as well as to expand the study over higher values of turbulence intensity, in order to present a more detailed study with empirical conclusions.